Empowering UMKM Members Of KSPPS Nusantara Through Optimizing Sharia Financing For Sustainable Economic Growth - syuhada' syuhada'; Elis Zunita Anzar Wati; Anggilah Mawarni; Umu Farikhatus Sa'bandiyah (Shof Journal of Social Impact, 2024)
The program "Empowering MSMEs of KSPPS Nusantara Members through Optimizing Sharia Financing for Sustainable Economic Growth" aims to empower MSMEs that experience limited access to financing and low financial literacy. The subjects of service are members of KSPPS Nusantara in Sawo Village, Dukun, Gresik. This program uses a Participatory Action Research (PAR) approach with stages of problem identification, joint action planning, sharia financial literacy training, and business assistance. The results of the service show an increase in financial literacy, changes in business management behavior, and the formation of sustainable sharia-based local institutions. The emergence of local leaders and increased access to financing are also positive impacts of the program. This program has succeeded in encouraging inclusive economic growth with a fairer sharia financing scheme.